2014
DOI: 10.1136/injuryprev-2013-041133
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in unintentional injuries between indigenous and non-indigenous children: a systematic review

Abstract: Indigenous children experience a significantly higher burden of morbidity and mortality from unintentional injuries across different indigenous communities worldwide. Most of these injuries are highly preventable, presenting substantial potential to improve indigenous child health. However, there is limited evidence to illuminate the underlying risk factors for unintentional injuries in indigenous children, and this is a priority for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
4
33
1
Order By: Relevance
“…Risks in overall injury dropping by 69% for the Aboriginal population and by 66% for the total BC population are cause to celebrate. These results showing decreases are consistent with previously published results both for all ages of the Aboriginal and total population of BC (British Columbia Vital Statistics Agency 2004) and for overall child and youth injury hospitalization rates worldwide (Möller et al 2015; Mytton et al 2012; WHO World Health Organization 2002), and within Canada (Oliver and Kohen 2012; Alaghehbandan et al 2010). All major types of injury and causes of injury showed decreases in rates over time for both populations, which is contrary with US studies which show levelling of rates or even increases (U.S. Department of Health and Human Services, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Risks in overall injury dropping by 69% for the Aboriginal population and by 66% for the total BC population are cause to celebrate. These results showing decreases are consistent with previously published results both for all ages of the Aboriginal and total population of BC (British Columbia Vital Statistics Agency 2004) and for overall child and youth injury hospitalization rates worldwide (Möller et al 2015; Mytton et al 2012; WHO World Health Organization 2002), and within Canada (Oliver and Kohen 2012; Alaghehbandan et al 2010). All major types of injury and causes of injury showed decreases in rates over time for both populations, which is contrary with US studies which show levelling of rates or even increases (U.S. Department of Health and Human Services, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…An international review reported that Canadian studies of children and youth showed greater disparity between Aboriginal and non-Aboriginal children than studies elsewhere (Möller et al 2015). The studies included in Möller et al (2015)’s review were from countries (USA, Australia and New Zealand) with similar colonial histories and socioeconomic status as Canada; therefore, it is curious that Canadian studies show greater disparity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations